2021
DOI: 10.3390/molecules26216688
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caryophyllane Sesquiterpenes in the Entourage Effect of Felina 32 Hemp Inflorescence Phytocomplex in Triple Negative MDA-MB-468 Breast Cancer Cells

Abstract: Cannabis sativa L. crops have been traditionally exploited as sources of fibers, nutrients, and bioactive phytochemicals of medical interest. In the present study, two terpene-rich organic extracts, namely FOJ and FOS, obtained from Felina 32 hemp inflorescences collected in June and September, respectively, have been studied for their in vitro anticancer properties. Particularly, their cytotoxicity was evaluated in different cancer cell lines, and the possible entourage effect between nonintoxicating phytocan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The CB2 up-regulation induced by α-humulene, eugenol, and harpagoside is supported by the activation of CB2 induced by β-caryophyllene and by the action of other compounds present in the H. procumbens root extract, which may also affect other pathways. Potentiating properties for both eugenol and caryophyllane sesquiterpenes, such as β-caryophyllene and α-humulene, have been highlighted when these molecules were administered in combination with anticancer drugs or herbal phy-tocomplexes [42,43]. Particularly, the synergic effects of caryophyllane sesquiterpenes have been found to be associated with the inhibition of efflux pumps, which leads to the intracellular accumulation of other substances [44].…”
Section: Discussionmentioning
confidence: 99%
“…The CB2 up-regulation induced by α-humulene, eugenol, and harpagoside is supported by the activation of CB2 induced by β-caryophyllene and by the action of other compounds present in the H. procumbens root extract, which may also affect other pathways. Potentiating properties for both eugenol and caryophyllane sesquiterpenes, such as β-caryophyllene and α-humulene, have been highlighted when these molecules were administered in combination with anticancer drugs or herbal phy-tocomplexes [42,43]. Particularly, the synergic effects of caryophyllane sesquiterpenes have been found to be associated with the inhibition of efflux pumps, which leads to the intracellular accumulation of other substances [44].…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects on macrophage function have been found for β-caryophyllene oxide, albeit highlighted in just one study [33]. Considering the structural similarity with β-caryophyllene and the recently highlighted ability to modulate CB2 receptor expression [2], it is conceivable that it can act like the lead compound, thus suggesting the need for further investigation.…”
Section: Discussionmentioning
confidence: 53%
“…This is a critical methodologic feature as high impurity levels can dramatically affect the activity of the tested compounds, leading to unreliable results. Indeed, in our previous study, we highlighted that very low concentrations of caryophyllane sesquiterpenes were able to synergize cannabidiol cytotoxicity [2]; therefore, considering the possible modulating effects of minor compounds, the true mechanism of the tested substance is not ensured. As suggested by the best practices to be applied in phytopharmacological research, details about compound purity should be reported; in particular, the use of high purity (95-99%) compounds is recommended [66].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Synergistic effects of β-caryophyllene oxide towards sorafenib were also confirmed in a xenograft model of liver cancer [20]. More recently, we reported the potentiating effects of caryophyllane sesquiterpenes towards cannabidiol and harpagoside in hemp and devil's claw extracts, respectively [18,22].…”
Section: Introductionmentioning
confidence: 55%